Prevalence of Erectile Dysfunction in Patients With Abdominal Aortic Aneurysm: An Exploratory Study - de Donato, Gianmarco; Pasqui, Edoardo; Gargiulo, Bruno; Casilli, Giulia; Ferrante, Giulia; Galzerano, Giuseppe; Cappelli, Alessandro; Palasciano, Giancarlo (Frontiers in Cardiovascular Medicine, 2022)
Introduction Erectile dysfunction (ED) is defined as the recurrent inability to achieve and maintain a satisfactory erection for sexual intercourse. Many studies have highlighted that ED shares common cardiovascular risk factors with cardiovascular disease. No data are reported about the prevalence of ED in patients with the abdominal aortic aneurysm (AAA). The aim of our study was to investigate the preoperative information given about sexual functions of patients undergoing endovascular aneurysm repair (EVAR) and to compare it with the presence and severity of steno-occlusive atherosclerotic lesions of the pelvic arterial tree at pre-operative Computed Tomography Angiography (CTA). Methods We prospectively enrolled all men patients who underwent elective EVAR from September to November 2021. Preoperative ED was evaluated using the International Index of Erectile Function (IIEF-5) questionnaire. Preoperative imaging was routinely performed with CTA scan of the abdominal aorta and iliac-pelvic district. An innovative score of pelvic arterial disease associated to AAA was defined, dividing the iliac district in 4 zones attributing a grading of severity for each zone bilaterally (score ranges 0–24). Linear regression analysis was used to correlate IIEF-5 score to anatomical score of pelvic arterial steno-occlusive disease. Results A total of 25 patients were enrolled. Median age was 74 ± 5.3 years. IIEF-5 average score was 14.8 ± 7.1. Eight cases (32%) had severe ED; one case (4%) had moderate, five patients (20%) had mild to moderate ED; five patients (20%) had mild ED, and 6 (24%) patients had no ED. CTA evaluation revealed an average anatomical score of 7.9 ± 4.5. Pelvic disease was considered moderate-severe in 20 cases (80%) and not significant in 20% (five cases). Linear regression analysis confirmed the hypothesis that a more diseased pelvic arterial tree was correlated to a more severe ED (Y = −1.531* × + 26.35 [slope CI: −1.946 to −1.117, p < 0.0001]). Conclusion Although typically unreported, the prevalence of ED associated to AAA was found to be high. A vasculogenic origin of ED in patients with AAA is plausible and may be easily confirmed by the evaluation of pelvic arterial distribution at angio-CT performed for EVAR planning. Our proposed “MAPPING AND SCORING SHEET” may help to identify the vasculogenic origin of ED in AAA patients.